Organization of lipid centers operation in the Russian Federation — new opportunities - M. V. Ezhov; O. L. Barbarash; M. I. Voevoda; V. S. Gurevich; N. N. Vezikova; D. I. Sadykova; I. V. Sergienko; V. V. Kashtalap; A. N. Meshkov; D. V. Duplyakov; A. A. Sokolov; S. A. Boytsov (Российский кардиологический журнал)
Project of the Russian National Atherosclerosis SocietyIn 2016, Guidelines on the medical care organization to the patients with hereditary atherogenic lipid disorders in the regions of Russia were published, which described and presented the principles of routing patients with hereditary dyslipidemia and the organization of medical care for them within the current regulatory documents. In December 2018, the Russian Ministry of Health approved clinical guidelines for the diagnosis and treatment of familial hypercholesterolemia. Thus, persons with a severe hereditary dyslipidemia were able to get free medication with expensive lipid-lowering drugs and receive apheresis. Following the European ones, the Russian guidelines on the management of lipid metabolism disorders were updated: lower target low density lipoprotein cholesterol levels were adopted. In the Russian population, there is a high prevalence of hypercholesterolemia, including familial monogenic and polygenic types. Therefore, timely detection and routing to a lipid center or an office to a specialist (cardiologist, lipidologist), adequate and modern prescription of lipid-lowering therapy will make an important contribution not only to secondary, but also to primary prevention of atherosclerotic cardiovascular complications.